"Listening to the Multiple and Multispecies Voices of the Crisis": Climate Change in Two Cetacean Fictions by Vandana Singh. Issue 1 (2nd January 2023) - Baishya, Amit R.
Abstract: This article reads two cetacean tales—"Entanglement" and "Requiem"—by the prominent South Asian writer of science fiction, Vandana Singh, to evaluate her portrayal of ordinary dimensions of living and existing in situations impacted by climate change. While cetaceans often function as an exotic alien other in science fiction and in cultural fantasies, Singh places her cetacean tales among Indigenous communities in the North Arctic region. Communities like the Inuits and the Iñupiat share relationships of collaborative reciprocity with cetaceans like belugas and bowhead whales. Deploying the geographer's Chie Sakakibara's concept of "cetaceousness"—complex, co-constitutive and quotidian relationships among humans and cetaceans in the North Arctic—this article studies Singh's merger of realism and speculation in her representation of the impact of global warming on populations for whom climate change is not a catastrophe waiting in the future, but whose effects have seeped into the minutiae of the everyday and the ordinary.